Design study of the UELV-10/5-15S accelerating structure - Chetverikov, I.O.; Kalinichenko, M.A.; Ryabtsov, A.V.; Zuev, Yu.V. (Вопросы атомной науки и техники, 2001)
The UELV-10/5-15S electron linear accelerator is intended for use in the sterilization applications. Electron energy can be continuously variable from 5 to 10 MeV by changing the accelerated beam current. The 2 m long accelerating structure includes a standing wave buncher, a travelling wave accelerating part and an on-axis resonant RF load. Beam dynamics calculations have been made taking into account space charge forces. Optimization of the buncher parameters permitted to achieve capture efficiencies up to 75% with no external focussing. It is expected that beam powers from 13 kW to 15 kW will be obtained in the 5 to 10 MeV energy range.